Identification of AP2/ERF transcription factors in Tetrastigma hemsleyanum revealed the specific roles of ERF46 under cold stress - Xie, Zhuomi; Yang, Chuyun; Liu, Siyi; Li, Mingjie; Gu, Li; Peng, Xin; Zhang, Zhongyi (Frontiers in Plant Science, 2022)
Tetrastigma hemsleyanum (T. hemsleyanum) is a traditional medicinal plant that is widely used in China. Cultivated T. hemsleyanum usually encounteres cold stress, limiting its growth and quality at key developmental stages. APETALA2 (AP2)/ethylene-responsive factor (ERF) transcription factors (TFs) comprise one of the largest gene superfamilies in plants, and are widely involved in biotic and abiotic stresses. To reveal the roles of AP2/ERF TFs during T. hemsleyanum development, 70 AP2/ERF TFs were identified in T. hemsleyanum. Among them, 18 and two TFs were classified into the AP2 and RAV family, respectively. The other 50 TFs belonged to the ERF family, and were further divided into the ERF and (dehydration reaction element binding factor) DREB subfamilies. The ERF subfamily contained 46 TFs, while the DREB subfamily contained four TFs. A phylogenetic analysis indicated that AP2/ERF TFs could be classified into five groups, in which 10 conserved motifs were confirmed. Several motifs were group- or subgroup- specific, implying that they were significant for the functions of the AP2/ERF TFs of these clades. In addition, 70 AP2/ERF TFs from the five groups were used for an expression pattern analysis under three low temperature levels including -4°C, 0°C and 4°C. The majority of these AP2/ERF TFs exhibited a positive response to cold stress conditions. Specifically, ThERF5, ThERF31, ThERF46 and ThERF55 demonstrated a sharp response to cold stress. Moreover, AP2/ERF TFs exhibited specific expression patterns under cold stress. Overexpression and RNA interference indicated that ThERF46 has specific tolerance to cold stress. These new insights provide the basis for further studies on the roles of AP2/ERF TFs in cold stress tolerance in T. hemsleyanum.